UPAYA PENGURUS KOPERASI DALAM MENINGKATKAN KESEJAHTERAAN ANGGOTA KOPERASI SIMPAN PINJAM (KSP) BOBATO DI KOTA TERNATE - Ahmad, Iswadi M (Jurnal Pendidikan dan Ekonomi (JUPEK), 2023)
The aim of this research is to determine the strategy of cooperative administrators in improving the welfare of Bobato cooperative members. This research is a type of qualitative research. Research data was obtained through observation, interviews and documentation. The research subjects were 20 cooperative members and administrators of the Bobato cooperative. Meanwhile, the data analysis technique uses qualitative descriptive data analysis techniques. The data analyzed through percentage analysis via surveys on research subjects was strengthened by the results of analysis from in-depth interviews and KSP Bobato documents. The research results show that the cooperative management strategy is to provide the best service to members, make it easier for members to fulfill their needs, such as providing loans to cooperative members at low interest rates, providing regular counseling, training and education for members, and continuing members' studies. cooperatives at undergraduate and graduate levels. Meanwhile, the distribution of remaining business profits received by each member experiences an increasing trend every year. So that every member of the cooperative can feel the value of the economic benefits received by each member of the Babato Savings and Loans Cooperative which is positive for the members